Chromatographic determination and risk assessment of sulfamethoxazole in the surface water of Laguna De Bay - dela Rosa, Kriserla Paula D.​; Villafuerte, Jillian Elaine A.​; Vivo, Ria Marcelle T.​ (2017)
The rise of antimicrobial resistance is recognized as a major clinical and public health problem. Therefore, the misuse of antibiotics as human and veterinary medicine and its subsequent excretion in the environment posed as a serious health and ecological concern. Unfortunately,there is a considerable limited research studies in regards with this problem in the Philippines.Hence, there is a need for further studies. This study focused on the detection of sulfamethoxazole in the surface water of Laguna Lake using ultra performance liquid chromatography(UPLC) pretreated with solid phase extraction(SPE) and assessment of its impact on humans and the environment using the prescribed European guidance for environmental risk assessment of APls. Results show the sulfamethoxazole was detected at varying levels of20.05 mcg/L to 28.94mcg/L atthethree sample sites in Laguna Area, Calamba, Los Baños and Victoria. In relation to these values,among the aquatic species, the risk of ecotoxicity was most notable for cynobacteria,crustacians,and other flowering plants. However, in humans, no risk appears for the indirect pressure.